Analisis Pengaruh Modal Usaha, Inovasi Produk, dan Strategi Pemasaran terhadap Pendapatan UMKM Kuliner Berbasis SPSS - Mohammad Khuluqin Adim; Ainur Indra Bahtiar; Lukmanul Hakim; Miftahul Jannah; Samsul Hadi; Arif Andi Prasetya (PT Cendekia Education Center, 2026)
This study aims to analyze the influence of Business Capital, Product Innovation, and Marketing Strategy on MSME Revenue using a quantitative approach through multiple linear regression analysis based on SPSS. The research data were obtained from questionnaires distributed to 25 MSME respondents. The variables studied were Business Capital (X₁), Product Innovation (X₂), Marketing Strategy (X₃), and MSME Revenue (Y). Data analysis techniques used included multiple linear regression, F-test (simultaneous), t-test (partial), and coefficient of determination (R²) to determine the contribution of the independent variables to the dependent variable. The results showed a correlation coefficient (R) of 0.354, indicating a low relationship between Business Capital, Product Innovation, and Marketing Strategy on MSME Revenue. The coefficient of determination (R²) of 0.126 indicates that 12.6% of the variation in MSME Revenue can be explained by the three independent variables, while the remaining 87.4% is influenced by factors outside the study. The results of the simultaneous test (F-test) obtained a significance value of 0.410 (>0.05), indicating that Business Capital, Product Innovation, and Marketing Strategy collectively had no significant effect on MSME revenue. Furthermore, the results of the partial test (t-test) showed that Business Capital had a significance value of 0.308, Product Innovation 0.237, and Marketing Strategy 0.954, indicating that all independent variables individually had no significant effect on MSME revenue. Based on the results of the study, it can be concluded that Business Capital, Product Innovation, and Marketing Strategy did not significantly influence MSME revenue, either simultaneously or partially. Therefore, attention is needed to consider other factors that could potentially influence business revenue, such as service quality, business location, number of customers, and business management capabilities.